2020
DOI: 10.1051/0004-6361/202039185
|View full text |Cite
|
Sign up to set email alerts
|

ATOMIUM: A high-resolution view on the highly asymmetric wind of the AGB starπ1Gruis

Abstract: The nebular circumstellar environments of cool evolved stars are known to harbour a rich morphological complexity of gaseous structures on different length scales. A large part of these density structures are thought to be brought about by the interaction of the stellar wind with a close companion. The S-type asymptotic giant branch (AGB) star π1Gruis, which has a known companion at ∼440 au and is thought to harbour a second, closer-by (< 10 au) companion, was observed with the Atacama Large Millimeter/subm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 88 publications
2
39
1
Order By: Relevance
“…Such a structure had already been found in the S-type star π 1 Gru (Sahai 1992), which was later confirmed by higher spatial resolution observations using ALMA (Doan et al 2017). This object has a G0V companion (Feast 1953) and possibly a second, much closer companion (Homan et al 2020). In Hoai et al (2014), we reported for RS Cnc the possible presence of a companion seen in the 12 CO(1-0) channel maps at velocities around 6.6 km s −1 and located about 1 west-northwest of the continuum source.…”
Section: Cosupporting
confidence: 65%
“…Such a structure had already been found in the S-type star π 1 Gru (Sahai 1992), which was later confirmed by higher spatial resolution observations using ALMA (Doan et al 2017). This object has a G0V companion (Feast 1953) and possibly a second, much closer companion (Homan et al 2020). In Hoai et al (2014), we reported for RS Cnc the possible presence of a companion seen in the 12 CO(1-0) channel maps at velocities around 6.6 km s −1 and located about 1 west-northwest of the continuum source.…”
Section: Cosupporting
confidence: 65%
“…AlF, AlCl, NaCl, KCl) were detected towards π 1 Gru, the only other S-type star in the ATOMIUM survey. This may be partly because the unusual torus + bipolar structure of the CSE of π 1 Gru (Doan et al 2017;Homan et al 2020) could make it harder to detect less abundant molecules or might even interfere with molecule formation. We are not aware of any other detections of halide molecules towards S-type stars with ALMA.…”
Section: S-type Agb Starsmentioning
confidence: 99%
“…These values are also typical of the line data cubes in each configuration. The procedure for constructing the final cubes of CO and SiO is identical to what is described by Homan et al (2020b), with a few minor variations, notably in weighting (see next paragraph) during imaging to produce the desired resolutions as given in Table 2.…”
Section: Data Acquisition and Reductionmentioning
confidence: 99%
“…Considering that the void in R Hya consistently appears in approximately the same channels and at the same place in different molecules observed in the atomium survey, the presence of a photodissociating companion (i.e., either a cool WD or hot main-sequence star) cannot be immediately excluded. Depending on its properties, such a companion could easily remain hidden in spectra or SEDs, as was the case for the WD companion of EP Aqr (Homan et al 2020a), or the companion of π 1 Gruis (Homan et al 2020b). It must be noted, however, that it is unlikely that R Hya possesses two companions of significant mass within a radius of 50 au, since this would make the system highly unstable, implying that it would probably not have survived up to the AGB phase.…”
Section: Compact Emission Voidmentioning
confidence: 99%